A bidirectionally reversible light-responsive actuator based on shape memory polyurethane bilayer. (May 2021) - Wang, Tianjiao; Zhao, Jun; Weng, Chuanxin; Wang, Tong; Liu, Yayun; Han, Zhipeng; Zhang, Zhong
Abstract: In this work, a simple method is proposed for the preparation of bidirectionally reversible light-responsive shape memory polyurethane (SMPU) bilayer. This SMPU bilayer consists of a 4, 4-azodibenzoic acid (Azoa) containing SMPU (SMPU-Azoa) layer and a carbon black (CB) containing SMPU (SMPU-CB) layer. A reversible deformation is realized when the two sides are exposed to ultraviolet (UV) and infrared (IR) lights, respectively. The working mechanism is the trans – cis isomerization of SMPU-Azoa layer and the photo-thermal effect of SMPU-CB layer. The effect of the filler content and the thickness ratio of bilayer is systematically studied. The reversible bending angle of the SMPU bilayer can exceed 30° in 16 s for one cycle when the Azoa and CB contents are 5 wt% and 0.5 wt%, respectively, and the thickness ratio of SMPU-Azoa layer to SMPU-CB layer is 1/1.3. Furthermore, a micro-robot based on such LSMP bilayer is demonstrated.